Non Strabismismic Binocular Vision Anomalies Among Schoolchildren Aged 7-17 In Deli Serdang, Indonesia - Feiruz Hamid Umar Bahasywen; Mohd Zaki Awg Isa (CV. AFDIFAL MAJU BERKAH, 2025)
The non strabismic binocular vision anomalies is one of the visual impairment that prevalent among children and this anomalies may negatively impact on child’s school performance and future learning ability, diagnosis and treatment of binocular vision anomalies should be a primary concern. This study employed a cross-sectional method to evaluate binocular vision dysfunctions among school children in Deli Serdang, Indonesia. A history taking followed by standard subjective refraction procedures were performed for refractive errors assessment. Binocular vision assessments were done using standard vergence and accommodation tests. A total of 114 subjects (mean age = 11.81 ± 3.38; female 54%, male 47%) had completed the study. The prevalence of non-strabismic binocular vision anomalies (NSBVA) was 52% (n=60). The convergence insufficiency was the highest (23%) type of NSBVA, followed by accommodative excess (10%), accommodative insufficiency (10%), accommodative infacility (7%) and accommodation insufficiency + convergence insufficiency (3%). There was no significant difference between all the types of NSBVA and across the age group and gender. This study shows that the prevalence of NSBVA is high in the schoolchildren population in North Sumatera. There is a need for a robust vision screening strategy for early detection and intervention of NSBVA to reduce future visual impairment and blindness that may impact school performance among school children in Indonesia